Innovation in Learning Simple Present Tense And Prsent Continiouse Tense Through Visual Media to Facilitate Students’ Understanding - Dalimunthe, Abdu Rohim Ilhami; Riadi, Kaisyah Abellia; Margaretha, Santa; Aulia, Yesika; Ramadani, Nanda (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Mastery of grammar, particularly tenses, is a fundamental aspect of learning English. However, many students face difficulties in distinguishing and understanding the use of the Simple Present Tense and the Present Continuous Tense due to their abstract nature and the need for contextual understanding. This study aims to examine the effectiveness of using interactive visual media as an instructional innovation to enhance students’ comprehension of these two tenses. Using a descriptive qualitative approach, the study was conducted with junior high school students through the application of visual aids such as illustrative images, infographics, and short animations representing real-life contexts in sentences. The results show that the use of visual media not only increases students’ interest in the material but also helps them grasp the differences in time and context between the two tenses more concretely. Moreover, students became more actively engaged in the learning process, as the visual involvement stimulated their interest and focus. The conclusion of this study is that interactive visual media can serve as an effective solution to students' difficulties in understanding the Simple Present Tense and Present Continuous Tense, as well as create a more enjoyable and meaningful learning environment.